2010
DOI: 10.1186/1744-9081-6-70
|View full text |Cite
|
Sign up to set email alerts
|

Categorical and continuous - disentangling the neural correlates of the carry effect in multi-digit addition

Abstract: BackgroundRecently it was suggested that the carry effect observed in addition involves both categorical and continuous processing characteristics.MethodsIn the present study, we aimed at identifying the specific neural correlates associated with processing either categorical or continuous aspects of the carry effect in an fMRI study on multi-digit addition.ResultsIn line with our expectations, we observed two distinct parts of the fronto-parietal network subserving numerical cognition to be associated with ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 52 publications
(100 reference statements)
4
57
1
Order By: Relevance
“…Anderson et al [18] reviewed the evidence that the ANG, particularly the right, is associated with reasoning about intentions. Also the MTG is involved in deductive reasoning [28], [29], reasoning about intentions [30], and arithmetic competence [31], [32].…”
Section: Resultsmentioning
confidence: 99%
“…Anderson et al [18] reviewed the evidence that the ANG, particularly the right, is associated with reasoning about intentions. Also the MTG is involved in deductive reasoning [28], [29], reasoning about intentions [30], and arithmetic competence [31], [32].…”
Section: Resultsmentioning
confidence: 99%
“…This means that magnitude-related processing will be the most probable solution strategy the larger the unit and decade sum, respectively. Indeed, with increasing values of unit and decade sum Klein and colleagues [34] observed activation in brain areas associated with magnitude-related processing. By contrast, with decreasing unit and decade sum, addition problems get easier (e.g., 2+3) and may even be solved relying on arithmetic fact retrieval.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, recent studies indicated a shift in brain activation from frontal to parietal regions with arithmetic training [21], [29][31] and age [32]. Moreover, first evidence for a flexible interplay of different numerical representations in one and the same task came from fMRI studies using a parametric modeling approach to a number bisection task [33] and to mental addition [34]. The method of parametric modeling seems to be particularly suited to investigate contributions of different representations, because it allows for defining parametric regressors representing several dimensions of complex stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations